A Comprehensive Literature Review on The Role of Leadership Styles In Implementation Of Strategic Plans In Malawi State-Owned Enterprises - Mfuni, Geofrey Joseph (LPPM of NAROTAMA UNIVERSITY, 2025)
The development of strategic plans has become sort of a cliché in recent years. However, studies show that developing a strategic plan is way easier than implementing it. The aims of the study are to find out the role that leadership styles play in the implementation of strategic plans and to recommend the most appropriate leadership style for use during the implementation of strategic plans. Data for this study was sourced from relatable previous studies from across the globe and those close to Malawi. The literature was sourced online using Google Scholar search engine. The findings show that indeed, leadership styles have a role to play when it comes to the implementation of strategic plans. The most common leadership styles are transformational, autocratic, democratic, laissez-faire and transactional. The study recommends the use of all other leadership styles except autocratic which is deemed to be oppressive to the team. All the other leadership styles encourage teamwork, commitment and working towards the same goals.